Dental Caries Investigation in Children Controlled for an Educative and Preventive Oral Health Programme - Pereira Pinto, Leila Maria Cesario; Cesario Pereira Maluf, Eliane Mara; Inagaki, Luciana Tiemi; Pascon, Fernanda Miori; Puppin-Rontani, Regina Maria; Jardim Júnior, Elerson Gaetti [UNESP] (Quintessence Publishing Co Inc, 2020)
Purpose: To evaluate the association of dental caries with behavioural, socioeconomic and cultural factors; and Streptococcus mutans (SM) levels in the saliva and oral hygiene index of children aged 4 and 6 years old placed in an oral health programme. Materials and Methods: This study was an analytic cross-sectional oral health survey conducted over a 9-month period. A total of 466 children aged 4 and 6 years old were included for evaluation of SM levels in saliva, simplified oral hygiene index and dental caries activity. Results: High SM levels were associated with dmft index, toothbrushing without parental assistance, deficient oral hygiene and ingestion of sweet foods. Deficient oral hygiene was found in children aged 4 years old and with three or more siblings. Dental caries was associated with low family income, deficient oral hygiene, sucrose ingestion by children younger than three years old, bottle-feeding habit and low parental compliance. Conclusions: High SM levels in saliva, deficient oral hygiene and high frequency of sucrose ingestion had association with dental caries in children. Cultural, socioeconomic and behaviour factors indirectly influenced the onset of dental caries.
Keywords: dental caries; child; oral health; preventive health services